Perbanyakan Nematoda Patogenik Serangga (Rhabditida: Steinernema dan Heterorhabditis) pada Media In Vitro Cair Statik - -, chaerani -; Suhendar, M Ace; Harjosudarmo, J - (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
ABSTRACTIn Vitro Culture of Entomopathogenic Nematodes(Rhabditida: Steinernema and Heterorhabditis) in StaticLiquid Media. Chaerani, M. Ace Suhendar, and J.Harjosudarmo. Entomopathogenic nematodes belongingto genera Steinernema and Heterorhabditis are potentiallymost effective and safe biological control agents for insectpests, especially for soil dwelling insects and those living incryptic habitats. Field application of the nematodes is stillhampered by supply of large number of infective juvenile(IJ) nematodes. Five published in vitro media along with itstwo modifications were tested for mass propagations of twoindigenous nematodes (H. indicus PLR2 and SteinernemaT96) and one commercial strain (S. carpocapsae #25).Varying levels of IJ yields were observed across thereplications and experiments. Medium F that contained 1.0%yeast extract, 2.5% egg yolk, and 4.0% soy oil yielded thehighest IJ numbers of H. indicus PLR2 (1.5Ã105 IJ ml-1) andof S. carpocapsae #25 (2.9Ã105 IJ ml-1), whereas the widelyused medium B, which is based on homogenized chickenoffal (40%), yielded the highest number of Steinernema T96(5.8Ã104 IJ ml-1). The IJâs quality, as measured by theirmorphometrics and pathogenicities, were generallyimpaired, indicating the lack of essential nutrient(s) in themedia. Optimization of the propagation media is thereforestill needed to increase IJâs quantity and quality to achievethe required standard for commercial scale of artificialpropagation.